Comment on "Accurately measured precipitate-matrix misfit in an AlMgSi alloy by electron microscopy". (1st January 2017) - Ehlers, F.J.H.; Dumoulin, S.
Abstract: Drawing attention to a recently reported [S. Wenner, R. Holmestad, Scripta Mater. 118 (2016) 5] close agreement of experimentally and theoretically determined strain fields for the AlMgSi alloy precipitate β″ in fcc Al, we argue that these results may indicate a non-negligible β″/Al misfit along the precipitate main growth direction. The consequences of such findings are discussed.